The Impact of ICT Training Through Wikis on In-Service EFL Teachers: Changes in Beliefs, Attitudes, and Competencies - Yamith José Fandiño Parra (Asociación Colombiana de Profesores de Ingles, 2012)
The development of information and communication technology (ICT) invites teachers to abandon traditional roles and act more as mentors, exploring the new media themselves as learners and thus acting as role models for their students (Fitzpatrick & Davies, 2003). For turning students into producers of online content and creating a collaborative learning environment, wikis appear to help foreign language teachers to infuse ICT in their classrooms (Kovacic, Bubas & Zlatovic, 2007). Within this context, results from an action research project carried out in four public schools suggest that beliefs, attitudes, and competencies can be impacted positively when working on the use of new technologies with in-service English teachers.